Pembuatan Jobsheet Sinkronisasi Generator pada Mata Kuliah Mesin-Mesin Listrik - Teguh Aimanto Daulay; Hansi Effendi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
The Job sheet in this study is a practical guide that contains the tools used, the materials used, the sequence of work instructions, the results of examinations, and conclusions regarding the practices that have been carried out in the laboratory. This research was motivated by the lack of creative and innovative media as student practicum media as well as the simple appearance of job sheets and the material presented was not attractive. This study aims to develop a valid job sheet for generator synchronization in the subject of electrical machines. This study uses the type of development R&D (research and development) with a 4-D model which consists of four stages without the deployment stage, namely defining, designing, and developing. The data collection instrument uses an evaluation sheet in the form of a questionnaire for validity. Job sheet validity test from material expert 1 is very good and material expert 2 is very good ​​with very appropriate information. The validation results from Media Expert 1 were good and Media Expert 2 was very good with very appropriate information. It can be concluded that this generator synchronization job sheet is very feasible to use in practice because it has been declared very valid.